International Journal of Middle East Studies - Middle East Studies Association (Cambridge Cambridge University Press, 1970)
The International Journal of Middle East Studies publishes original research on politics, society, and culture in the Middle East from the seventh century to the present day. The journal also covers Spain, southeast Europe, parts of Africa, South Asia, and the former Soviet Union, as well as other regions, for subjects of relevance to the Middle East. Contributions are welcome from across disciplines, including anthropology, comparative religion, cultural studies, economics, history, law, literature, philosophy, politics, sociology, and theology.
Published quarterly under the auspices of the Middle East Studies Association Full text articles are available from JSTOR : https://www.jstor.org/journal/intejmiddeaststu
Keywords: History; MIDDLE EAST SITUATION; POLITICAL CONDITIONS; ECONOMIC CONDITIONS; MIDDLE EAST; PERIODICALS